Visualization of gas-liquid flow pattern in a centrifugal pump impeller and its influence on the pump performance. (February 2021) - Zhao, Lin; Chang, Zhuang; Zhang, Zhenduo; Huang, Rui; He, Denghui
Abstract: The flow pattern in centrifugal pump is critical for better understanding the effect of inlet gas on the pump performance. In this study, the bubble dynamic behavior and its influence on the flow pattern in the impeller were investigated. The effects of inlet gas volume fraction, the liquid flow rate and the rotational speed on the flow pattern were analyzed. Then the effect of flow pattern on the pump performance were discussed. The results show that there are four typical flow patterns, i.e., the Bubble Flow, the Agglomerated Bubble Flow, the Gas Pocket Flow and the Segregated Flow, in the impeller. The bubble dynamic behaviors, such as the deformation, breakup and coalescence are closely related with formation of flow pattern in impeller. The flow pattern changed from Bubble Flow pattern to Segregated Flow pattern gradually as the inlet gas volume fraction increased. The gas carrying capability of pump was improved with the liquid flow rate and the rotational speed increasing. The pump performance rapidly deteriorated when the flow pattern in the impeller changed from the Gas Pocket Flow to the Segregated Flow. The liquid flow rate also affected the pump pressure increment and efficiency by changing the flow pattern in the impeller. Furthermore, the pressure increment and the efficiency of the pump increased as the rotational speed increased.